EVALUATION OF PHYSICO-CHEMICAL PROPERTIES AND P SORPTION CHARACTERISTICS OF SOIL WITH DIFFERENT LAND USE IN TIGONI, KIAMBU COUNTY, CENTRAL KENYA - Benard Kiplangat Rop; George N. Karuku; Caroline W. Nduhiu (Tropical and Subtropical Agroecosystems, 2022)
Background: Phosphorous is a limiting crop nutrient in highly weathered tropical soils due to fixation, and its availability for plants’ uptake is influenced by soil physico-chemical characterics, land use type and management practices.    Objective: To evaluate the relationship between selected physico-chemical properties and phosphorous sorption characteristics of a humic nitisol (Alfisol) from Tigoni, Kiambu County, central Kenya. Methodology: The soil was sampled from the same area with different land uses that include tea plantation, maize field and natural forest at 0-25, 25-50 and 50-75 cm depths.  P solution at the rates of 50, 100, 150, 200 mg P L−1 in a 24 h contact time were used in the study for maximum sorption. The data was analysed by simple regression and Pearson correlation analysis.  Results: The adsorption data was fitted more to Langmuir model (R2 = 0.9100-0.9994) compared to Freundlich (R2 = 0.6815-0.9971). The values of P sorption maxima ( ) determined by Langmuir model ranged from 3,333-5,000 mg kg-1 and bonding energies ( ) ranged from 0.2308-1.5385 L mg-1. The buffering capacity of soil ranged from 769-5000 L kg-1 and the external P requirement at 0.2 mg kg-1 (  ranged from 147-1176 mg P kg-1 both increasing with soil depth. P sorption maxima were negatively and significantly correlated with organic carbon (r2 = -0.700*) and Ca2+ (r2 = -0.703*) contents. The pH of soil and clay content were negatively correlated with adsorption parameters ( ) while Al content was positively correlated though none of them was statistically significant. Implication: The data revealed a highly P-sorbing soil particularly tea plantation, a situation that can be alleviated by management practices such as liming and enhancing soil organic matter content. Field experiments are however, recommended to validate the findings of this study. Conclusion: Land use type influences P-sorption capacity of soil hence, fertilizer recommendations should be based on soil physico-chemical characteristics besides crop nutrient requirements.